Behaviour of Migratory Gaddi Goats, Their Welfare Issues and Mitigation Measures (Indian Journal of Animal Production and Management, 2024)
The demand for sustainably produced  livestock products has been rising due to increasing  consumer awareness towards animal welfare. This  can be an opportunity for the migratory goat  production system as they are generally believed to  have enhanced welfare due to their naturalness.  The present review is focused on behaviour and  welfare of migratory Gaddi goats, which are  primarily reared by Gaddi tribe of Himachal  Pradesh. Gaddi goats spend most of daytime in  feeding and walking with little time spent on  standing, lying and rumination. Feeding was  undertaken through grazing predominantly at high hills and through browsing in bipedal stance during  lactation at low and mid-hills. Grooming activities  were most evident at post-kidding and during  lactation at low and mid-hills. Gaddi flocks generally  have higher welfare scores, however they also  faced welfare issues during their migration viz. lack  good quality pasture, poor body condition, non adoption of pain management practices, parasitism  (ecto and endo), abortions, lameness, rustling and  wildlife attack. The welfare was found to decrease  as the flock size increased. These goats showed  welfare advantages in environment, behaviour,  performance and health domains but disadvantage  in feeding domains.
Keywords: Migratory goats; behaviour; welfare issues; welfare assessment